Genetic Polymorphisms of Multidrug Resistance Gene-1 (MDR1/ABCB1) and Glutathione S-Transferase Gene and the Risk of Inflammatory Bowel Disease among Moroccan Patients - Nezha Senhaji; Yaya Kassogue; Mina Fahimi; Nadia Serbati; Wafaa Badre; Sellama Nadifi (Hindawi Limited, 2015)
Inflammatory bowel diseases (IBD) are multifactorial disorders resulting from environmental and genetic factors. Polymorphisms in MDR1 and GSTs genes might explain individual differences in susceptibility to IBD. We carried out a case-control study to examine the association of MDR1 (C1236T and C3435T), GSTT1, and GSTM1 polymorphisms with the risk of IBD. Subjects were genotyped using PCR-RFLP for MDR1 gene and multiplex PCR for GSTT1 and GSTM1. Meta-analysis was performed to test the association of variant allele carriage with IBD risk. We report that GSTT1 null genotype is significantly associated with the risk of CD (OR: 2.5, CI: 1.2-5, P=0.013) and UC (OR: 3.5, CI: 1.5-8.5, P=0.004) and can influence Crohn's disease behavior. The interaction between GSTT1 and GSTM1 genes showed that the combined null genotypes were associated with the risk of UC (OR: 3.1, CI: 1.1-9, P=0.049). Furthermore, when compared to combined 1236CC/CT genotypes, the 1236TT genotype of MDR1 gene was associated with the risk of UC (OR: 3.7, CI: 1.3-10.7, P=0.03). Meta-analysis demonstrated significantly higher frequencies of 3435T carriage in IBD patients. Our results show that GSTT1 null and MDR1 polymorphisms could play a role in susceptibility to IBD.